Exquisite Corpses and backward glances: European social anthropology 2019. (1st August 2020) - Martin, Dominic
Abstract : This article provides an overview of the main European social anthropology journals during 2019. It uses the concept of Exquisite Corpses, a technique devised by the Surrealists, an avant‐garde art group of the early 20th century, to suggest a practice of transmitting knowledge across periods of fracture. It argues that this process characterises the way that some aspects of social anthropology's canon continue to be transmitted and remain influential, despite having been superseded by time, fashion and changes in social and academic attitudes. A wide range of scholarship is highlighted. Topics focused on include time, relations, borders, bureaucracy, ethics, and the challenges faced by academics in general and anthropologists in particular. These challenges are driven by the emergence of an authoritarian spirit across a number of fields in Europe and beyond, continuing austerity following on from the economic crisis, and the consolidation of an audit culture that drives the university in an ever more neoliberal direction. Despite the current rigorous climate, European social anthropology continues to be vital and relevant.